Prediction of adverse clinical outcomes in pregnant women with severe and extremely severe forms of coronavirus infection - A. V. Shchegolev; R. E. Lakhin; A. A. Nikulin; S. G. Meshchaninova; V. F. Bezhenar (Вестник анестезиологии и реаниматологии)
The objective was to identify prognostic criteria for unfavorable outcome in pregnant women with severe and extremely severe forms of COVID-19 and to build a model for predicting clinical outcome.Materials and methods. The cohort single-center retrospective study was conducted, which included 83 patients who were treated in the intensive care unit (ICU) from January 1 to December 31, 2021. Of these, 13 patients had an unfavorable outcome – death, and 70 patients with a successful outcome – recovery. The differences in the main clinical and laboratory parameters of patients of both groups during hospitalization in the ICU and on the 3rd day of treatment (Δ – delta) were analyzed.Results. The Cox regression analysis identified laboratory parameters, the difference of which (Δ) on admission to the ICU and on the 3rd day of treatment is associated with the development of the unfavorable outcome (death). These indicators were used as variables in a linear regression equation. The equation for calculating the prognostic index met the criteria of a statistically significant model (sensitivity 84.6 %, specificity 85.7 %, area under the operating characteristic curve (AUROC – Area Under Receiver Operator Curve) – 0.959 (95 % confidence interval [95 % CI] 0.918 – 1.0).Conclusion. The calculation of the prognostic index can be an additional clinical tool that allows one to predict the development of an unfavorable outcome, concentrate the work of a multidisciplinary team, attract additional reserves of a medical institution and/or evacuate such patients to high-level hospitals.